Sociocultural factors in cardiology: previous knowledge de novo - E. O. Taratukhin (Российский кардиологический журнал, 2020)
Despite the progression in cardiovascular biomedicine, the issue of a person's social life and his social relations remains relevant. The impact on adherence to lifestyle changes and therapy, on risk factors such as stress or physical inactivity, is imperative and cannot be realized through biomedical methods alone. In the modification of sociocultural and psychosocial risk factors, the work of a doctor with a patient is the interaction of two subjects, who have experience in their lives. The article provides a brief analysis of the modern understanding of sociocultural aspects of cardiovascular processes and proposes the concept of identity as a unit of meaning in such a coordinate system. The modern understanding of the biosocial structure of a person makes it possible to move from the declarative principles of “treating the patient — not just the disease” to a scientific interdisciplinary and practical concept. The inclusion of a humanitarian knowledge about the structure of culture and society in modern biomedicine will provide a novel, constructive understanding of doctor-patient relationship.